Managing Laggards: The Importance of a Deep Sales Bench - Boichuk, Jeffrey P.; Bommaraju, Raghu; Ahearne, Michael; Kraus, Florian; Steenburgh, Thomas J. (Journal of Marketing Research, 2019)
Sales leaders often use threats of punishment to manage poor performers (i.e., laggards), but little research has examined the effect of these threats. The current research addresses this gap by investigating an intervention termed the “bench program” with a field-based quasi experiment and a randomized lab experiment. In the field, the company under study told salespeople in treatment districts that a trainee would replace them at the end of the year if they failed to hit their quota and placed last in their district. Difference-in-differences analyses of matched treatment and control groups show that the bench program had an immediate and sustained impact on performance. Moreover, laggards improved their performance more than higher performers, and salespeople with larger advice networks improved their performance more than salespeople with smaller advice networks. A lab experiment compares the bench program with a program that had the same threat of firing but did not have replacements in sight. Performance in the bench program exceeded that in the firing condition, indicating that the vividness of a threat can increase its deterrent value.